RETRACTED: Safety Evaluation of Antituberculosis Drugs During Pregnancy: A Systematic Review and Meta-Analysis - Zhou, Xiaomei; Fang, Guoying; Xie, Yaqing; Wei, Anqi; Huang, Feixiang (Frontiers in Surgery, 2022)
Background Pregnant women are a common group of people with tuberculosis,especially in patients infected with HIV at the same time. Antituberculosis drug prophylaxis is effective in reducing tuberculosis infection in pregnant women and fetuses after pregnancy, but its safety is still worthy of in-depth discussion. In this study, we conducted a systematic review and meta-analysis of reports on the use of antituberculosis drugs during pregnancy in recent years to provide evidence for clinical diagnosis and treatment. Methods The PubMed, Embase, Web of Science databases, Ovid, and clinicaltrials.gov were searched. Search for clinical randomized controlled studies and cohort studies on the use of antituberculosis drugs during pregnancy published in the databases from January 2000 to September 2021 was performed using the Stata 16.0 software after screening qualified bodies of literature. Results On the basis of the initial search of 408 articles, this study included a total of 8 articles and 2,563 patients after screening; meta-analysis results showed that preventive treatment with antituberculosis drugs did not increase the incidence of serious maternal adverse events [RR = 0.99, 95% CI (.88, 1.12), Z = −0.108, P = 0.914], did not increase drug hepatotoxicity [RR = 1.13, 95% CI (.9, 1.43), Z = 1.071, P = 0.284], did not increase the incidence of peripheral nerve disease [RR = 1.52, 95% CI (.85, 2.71), Z = 1.412, P = 0.158], did not increase maternal mortality [RR = 0.67, 95% CI (.27, 1.7), Z = −0.84, P = 0.401], and could significantly reduce adverse pregnancy outcomes [RR = 0.78, 95% CI (0.68, 0.89), Z = −3.581, P < 0.0001]. Discussion The use of antituberculosis drugs for preventive treatment during pregnancy is safe and can obtain better pregnancy outcomes.